PENGARUH KEDISIPLINAN TERHADAP KINERJA KARYAWAN PADA RS. IBNU SINA YBW UMI MAKASSAR - Megawhati Artiyany (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This research aims to find out the influence of discipline on employee performance in hospitals. Ibn Sina YBW Umi Makassar. The type of data used is qualitative and quantitative data, then the data source used, namely primary data and secondary data. The collected data is analyzed in a scriptive manner, meaning that the data obtained in the field is processed in such a way that it provides a systematic understanding, then statistical calculations are held with simple regression analysis, coefisen correlation coefficient of determination (r) and t-test, From the results of calculations obtained values of y = 17.51 + 0.63 x, while the value of correlation coefficient (r) of 0.527 and coefficient of determination (r2) of 27.77% and the remaining 22.23% It is influenced by other factors that were not studied. While the results of the distribution are: t (t-table) = 2,034, from the calculation of the distribution t (thitung) = 3,562, so that it can be known t (thitung) > t table (3,562 > 2,034, so that Ha received and rejected H0, which means, discipline has a significant positive effect on employee performance in hospital. Ibn Sina YBW UMI Makassar.